The Self-Regulation of Eating Attitudes in Sport Scale: Defining an Optimal Regulation Zone - Scoffier-Meriaux, Stéphanie; Paquet, Yvan (Frontiers in Psychology, 2022)
This study examines the hypothesis of a Zone of Optimal Regulation of Eating Attitudes in Sport (ZOREAS). The ZOREAS refers to a band, or zone within which athletes are most likely to optimize eating attitude regulation which should be associated with a low level of disordered eating. Scores outside this zone indicate a risk factor for eating disorders. One hundred and eleven volunteer athletes were recruited. Two variables were assessed: self-regulation of eating in sport, and eating attitudes and behaviors, measured with the French Self-Regulatory Eating Attitude in Sports Scale (SREASS), and the French version of the Eating Attitudes Test (EAT), respectively. Correlational analyses and an ANOVA were run. As expected, we observed a negative relationship between scores for the self-regulation of eating, and disordered eating attitudes in the sports context. To better-determine the ZOREAS, we ran a one-way ANOVA, which was significant for disordered eating attitudes. The plot of the interaction confirmed three trends: a high level of disordered eating attitudes (EAT scores over 20) is associated with a high level of self-regulation of eating attitudes (SREASS scores over 24); a medium level of disordered eating attitudes is associated with a low level of self-regulation of eating attitudes (SREASS scores under 19); a low level of disordered eating attitudes is associated with a medium level of self-regulation of eating attitudes (SREASS scores between 19 and 24). Thus, the ZOREAS was determined to be SREASS scores within the range 19–24. The ZOREAS may be useful to sports psychology practitioners who work with athletes.